2019
DOI: 10.1053/j.gastro.2018.10.001
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Recurrence of Primary Biliary Cholangitis After Liver Transplantation and Effects on Graft and Patient Survival

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e17. Learning Objective: Upon completion of this CME activity, successful learners will be able to identify the factors associated with recurrence of primary biliary cholangitis after liver transplantation and define its effect on graft and patient survival. 785 pts received Liver Transplant (LT) due to Primary Biliary Cholangitis (PBC) Global PBC Group 240 pts developed Recurrence of PBC Gastroenterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 38 publications
1
86
1
2
Order By: Relevance
“…The rate of rPBC after liver transplantation is reportedly as high as 37% at 10 years . Despite the high incidence, rPBC has not been shown to affect graft/patient survival until recently . In a non‐transplant setting, asymptomatic PBC patients are known to have a shorter life expectancy than the general population, and early initiation of UDCA administration reduces the risk of liver‐related failure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of rPBC after liver transplantation is reportedly as high as 37% at 10 years . Despite the high incidence, rPBC has not been shown to affect graft/patient survival until recently . In a non‐transplant setting, asymptomatic PBC patients are known to have a shorter life expectancy than the general population, and early initiation of UDCA administration reduces the risk of liver‐related failure .…”
Section: Discussionmentioning
confidence: 99%
“…Although approximately 30% of liver transplant recipients are diagnosed with recurrent PBC (rPBC), recurrence of PBC has been thought not to affect graft or patient survival . Recently, a multicenter cohort study showed that recurrence of PBC was associated with impaired survival . It is therefore important to assess disease recurrence after liver transplantation, and also to prevent recurrence or progression of PBC.…”
Section: Introductionmentioning
confidence: 99%
“…Given at 13‐15 mg/kg/d, ursodeoxycholic acid (UDCA) is the first‐line therapy used in PBC treatment for all disease stages, 35 with improvements in serum hepatic biochemistry, delayed histological progression, delayed development of esophageal varices, and improved transplant‐free survival 60,61 …”
Section: What Is First‐line Treatment For Pbc?mentioning
confidence: 99%
“…We read with great interest the study of Montano-Loza et al 1 regarding outcomes after liver transplantation for primary biliary cholangitis (PBC) and factors associated with its recurrence. We first want to congratulate the authors for their work reporting the largest multicenter cohort published, allowing the identification of risk factors of PBC recurrence like young age at liver transplantation, the presence of biochemical markers of cholestasis after transplantation, and the use of tacrolimus.…”
Section: Recurrence Of Primary Biliarymentioning
confidence: 99%
“…Reply. We thank Rayar et al and Moro et al, for their interest in our recent publication 1 and for highlighting some challenging issues regarding primary biliary cholangitis (PBC) recurrence after liver transplantation (LT).…”
mentioning
confidence: 99%